Health Protocol Implementation in Indonesia During the COVID-19 Pandemic - Alchamdani Alchamdani; Nadila Puspita Ningsi (Sean Institute, 2025)
The implementation of health protocols is a crucial strategy in controlling the spread of COVID-19. This study aims to describe the compliance level of mask-wearing and physical distancing in Indonesia and its relation to the number of COVID-19 cases during the pandemic. The study used a descriptive research design based on secondary data obtained from the Ministry of Health of the Republic of Indonesia and the National COVID-19 Task Force. The dataset covered all 34 provinces from January to August 2021 and included monthly and cumulative COVID-19 cases, as well as the percentage of compliance with mask-wearing and physical distancing. Data were analyzed descriptively and presented in figures to illustrate provincial differences and national trends. The findings show that as of August 2021, Indonesia recorded 4,089,801 confirmed cases, with the highest numbers in DKI Jakarta, West Java, and Central Java. Provinces with high mask-wearing compliance (above 85%) included Bali, the Special Region of Yogyakarta, East Java, and Central Kalimantan, while low compliance (below 70%) was observed in North Maluku, Bengkulu, and Maluku. Similarly, provinces with high physical distancing compliance (above 80%) were Bali, Yogyakarta, and East Java, while lower compliance rates were observed in North Maluku and Bengkulu. Descriptive analysis indicated that provinces with higher compliance levels generally experienced lower COVID-19 transmission rates. This study highlights the importance of public adherence to health protocols, particularly mask-wearing and physical distancing, in reducing the spread of COVID-19. Effective government policies, continuous public education, and community engagement are essential to maintaining high compliance levels. The findings suggest that behavioral and policy interventions must be strengthened and adapted to regional characteristics to ensure sustainable pandemic control in Indonesia.